Aspek Kemiskinan dalam Pembangunan Pedesaan - Kadiman Pakpahan (Bina Nusantara University, 2002)
Poverty can be measured by rice consumption rate indicator and income rate indicator. This article describes the major element of poverty. The major element of poverty is natural factor, cultural factor, and structural factor.